A Study of Victims of Human Trafficking from a Critical Victimology Perspective - Rino Ayahbi; Sigid Suseno; Wanodyo Sulistyani (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Indonesia applies the principle of non-punishment subject to the condition of “coercion,” which in law enforcement practice tends to be narrowly interpreted as physical coercion; as a result, many victims who have experienced psychological or economic exploitation, or exploitation through power dynamics, are still subject to criminal prosecution. The objective of this study is to analyze the limited application of the principle of non-punishment for victims of human trafficking under Article 18 of Law No. 21 of 2007 through the lenses of positive and critical victimology, as well as its alignment with international standards. The urgency of this research lies in Indonesia’s need to align its legal framework with the Palermo Protocol and ASEAN guidelines, which affirm non-punishment as an unconditional obligation. The method used is normative legal research employing legislative, case-based, and conceptual approaches, utilizing primary and secondary legal materials analyzed qualitatively. The novelty of this study lies in integrating victimological criticism of the construction of the “ideal victim” in judicial practice to demonstrate that the state’s labeling of victims often serves as the basis for criminalization. The research findings indicate that the application of the non-punishment principle in Indonesia does not yet align with international standards because it still treats victims as perpetrators and has not implemented early victim identification; therefore, a reformulation of Article 18 of the TPPO Law is necessary to align with international provisions within the framework of TPPO victim protection.